Experimental study on calculation model of labyrinth emitter discharge under subsurface drip irrigation - Wen, Hou; Dan, Bai; Wen, Zhou (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: For different texture of soils, the grain composition is different with significant changes. Since the emitter of subsurface drip irrigation (SDI) is buried in the soil, emitter discharge is influenced by soil properties. An experiment was conducted to investigate the relationship between the soil properties with emitter working pressure and emitter discharge of SDI. Selecting three different grain composition soils, and emitter working pressure, as well as soil clay content, soil bulk density and initial soil moisture content respectively as influence factors of emitter discharge of SDI, the experimental scheme was gained by uniform design. A calculation model for determination of the SDI emitter discharge was established by regression analysis with the first two kinds of soil test data, and its reliability was verified by the third kind of soil test data. The model is simple with high accuracy, easy to use, and lays the foundation to study hydraulic elements of SDI field network, especially taking the soil clay content as an influencing factor has widened the scope of application of the model. The achievement is of great significance for design and management of SDI.Keywords: subsurface drip irrigation, emitter, soil clay content, discharge, calculation modelDOI: 10.3965/j.ijabe.20140706.003 Citation: Hou W, Bai D, Zhou W. Experimental study on calculation model of labyrinth emitter discharge under subsurface drip irrigation. Int J Agric & Biol Eng, 2014; 7(6): 14－19.